Design of polling access control protocol in WSN based on FPGA - Long-jun LIU; Hong-wei DING; Qian-lin LIU; Zheng-gang LIU (Tongxin xuebao)
MAC(media access control) protocol is a direct link between physical and network layer,which is one of the key protocols to ensure high efficient communication.According to the characteristics of WSN (wireless sensor network) nodes,the design and implementation of polling access control protocol based on FPGA (field programmable gate array) were presented for the first time.The design made full use of the characteristics of flexibility and reconfigurability of FPGA.The method of combination of the hardware circuit description language Verilog HDL and the principle diagram was adopted,using Quartus II 8.0 to carry on the synthesis and routing,testing in the DE2.The design has the characteristics of good real-time,high reliability,strong portability,and can effectively reduce the transmission delay and improve the bus utilization.The designed system can be widely used in WSN,software radio network,ad hoc networks,military integrated service network,mobile communications networks,Internet of things as well as other fields.